PROJECT-BASED LEARNING EQUIPS UNDERGRADUATE STUDENTS WITH WORKPLACE SKILLS - Nur Shafiekah Sapan,; Siti Katijah Johari,; Nurul Ain Zulhaimi,; Siti Nurul Aishah Abdul Hamid,; Siti Aishah Ramli, (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2024)
The new emerging trend for recent employment is the employers expect the university graduates to have more than academic excellence to be employed. They prefer graduates who possess soft skills such as communication skills, creativity, teamwork, management, and problem-solving. As a result, many educators are forced to change and find a new teaching and learning strategy to be incorporated in the classroom that would facilitate the students to develop both academic as well as interpersonal skills which are commonly known as soft skills. The holistic approach of Project-Based Learning (PBL) which integrates learning through working collaboratively in a project and bringing in the authentic experiences of the real world beyond the classroom walls has proven that PBL is designed to do both. The present study aimed to investigate how PBL can prepare students with related workplace skills and their perception of PBL in developing their soft skills. A set of a questionnaire is designed and administered to 77 second-year students, who are taking English for Occupational Purposes subject at Universiti Malaysia Sabah Labuan International Campus. The result of the study showed that PBL has able to equip the students with work-related skills, and by completing the projects, they were able to improve their soft skills, mainly in communication and self-confidence. Hence, the findings of the study proved that PBL is a relevant approach in a classroom to help in developing students' soft skills.